Determinants of brand authenticity in the apparel industry of Pakistan: moderating role of entrepreneurial marketing - Mughal, Muhammad Raza (2023)
Brand authenticity is an important component of business especially in apparel industry as it is associated with integration of cohesive brand strategy. It is also associated with brand congruence and commercialization process of the brand. The factors which affects brand authenticity discussed in this study were, brand actual and ideal congruence, commercialization, brand Nostalgia and social media engagement. Moreover, Brand authenticity is also influenced by entrepreneur marketing strategy of business. Therefore, the study conducted aimed at investigating entrepreneurial marketing as a moderating variable. As the factors associated in building brand authenticity has influence on sales and revenue, therefore, a study was conducted in three main cities of Pakistan to investigate the impact of brand authenticity in apparel industry. The study focused on discussing the factors which influence brand authenticity. The research also emphasized on evaluating the moderating effect of entrepreneur marketing on these factors and discussed its relation with these factors in building brand authenticity. The three major cities of Pakistan involved in these study were Lahore, Karachi and Islamabad. These cities were chosen and sampling units and a total of 1800 participants were recruited with non-probability sampling method. The research emphasized on primary quantitative research design and primary data was collected using survey questionnaire. The study utilized 5-point Likert scale for the interpretation and analysis of the data. Furthermore, statistical approaches such as Data screening, Variance, measurement, and structural model were utilized for the analysis of the data. The outcomes of the study revealed that there is positive and significant impact of actual brand congruence, brand nostalgia, entrepreneurial marketing, ideal brand congruence and social media management on the brand authenticity. However, the effect of brand commercialization effect on the brand authenticity is negative and significant that indicates that brand commercialization negatively affects the brand authenticity in case study of apparel industry of Pakistan. Furthermore, the study also discusses practical implications and future directions of the study.